InsurTech development in Vietnam - THỊ THÙY DUNG, NGUYỄN (Tạp chí Nghiên cứu Khoa học Công đoàn, 2019)
Technology - Insurance (InsurTech) is an industry that includes companies that use technology to provide cheaper, faster,simpler and more efficient insurance services. InsurTech will be a trend that will change the entire insurance industry in the world in the nearfuture, breaking the traditional way of operating in the insurance industry for hundreds of years, changing buying behavior. and the modesof administration and administration of every insurance company.